ASUHAN KEPERAWATAN MASALAH PSIKOSOSIAL HARGA DIRI RENDAH SITUASIONAL PADA NY.R DENGAN HIPERTENSI DI KELURAHAN LIMO DEPOK - Muthiah Raihani Siregar (2023)
Background : Hypertension is defines as an increase in blood pressure beyond normal limits. Hypertension is a problem that is often found in elderly population due to biological changes in the cardiovascular system that reduce its ability to function. The impact that occurs in the elderly always need other people to help them when they are sick which causes the elderly to be unable to achieve their own integrity and makes the elderly's self-esteem low. This research was conducted to find out situational low self-esteem in the elderly and the right way of handling patients through situational low self-esteem nursing care with hypertension. Methods : This research was conducted using the case study method of nursing care of situational low self-esteem in Mrs.R with hypertension in Limo Depok Village from February 23 to February 28 2023. Data collection was carried out by means of interviews, observation and documentation. Result : The main diagnosis of Mrs.R's problem is Low Self-Esteem. Nursing intervention carried out in the form of monitoring self-deprecating verbalization, motivation to engage in positive verbalization for oneself, motivation to accept new things, disuse statements, beliefs, and experiences to increase self-esteem. Nursing implementation is carried out in accordance with nursing intervensions that have been made and nursing evaluations are carried out. Within 3x24 hours the problem of situational low self-esteem in Mrs.R was partially resolved. Conclusion : Nursing care given to Mrs.R is partially resolved, Mrs.R can carry out independent interventions with family help and support.